Cities of God Under Occupation: Settler Colonial Practices and Pacification in The Favelas of Rio De Janeiro and The Occupied Palestinian Territories - Pimenta da Silva, Amanda (AUC Knowledge Fountain, 2022)
The 2002 film ‘City of God’ tells an anecdotal story of violence in the favelas of Rio de Janeiro, and is a reminder that the societies we tend to take for granted can actually be a luxury. The film portrays the daily life of the peripheries of Rio and its relation with drug trafficking, crime, and poverty, and how it has deteriorated into a war zone so dangerous that anyone risk being shot to death. Thousands of miles away from the Brazilian slums there is another so-called city of God, or the city chosen by God to be the home’s capital of the chosen ones, which is believed by some to be the ‘Land of Israel’, and nowadays illegally occupies much of Palestinian territories. The occupied areas of Palestine – Gaza and the West Bank – similarly endure daily violent life with militarization and targeted killings policies. For the last decades, there has been a state of permanent conflict in both situations, in which the government wields the law in order to justify its construction of a narrative of warfare, based primarily in ‘the name of security’. This paper identifies policies of governance developed by the narratives of peace and security, and that is heavily applied in both cases, by drawing on the chore mechanism that sustain sovereignty in modern liberal democracies: its right to occupy and kill, which can be widely accepted, or at least not condemned, in circumstances of war. The central argument in this paper is that the existence of a metaphorical war – against terror or drugs – is necessary in both cases for the State to put forward a plan of social control and domination, which is carefully constructed within the legal order.